A novel dissociative steroid VBP15 reduces MUC5AC gene expression in airway epithelial cells but lacks the GRE mediated transcriptional properties of dexamethasone. (June 2016) - Garvin, Lindsay M.; Chen, Yajun; Damsker, Jesse M.; Rose, Mary C.
Abstract: Overproduction of secretory mucins contributes to morbidity/mortality in inflammatory lung diseases. Inflammatory mediators directly increase expression of mucin genes, but few drugs have been shown to directly repress mucin gene expression. IL-1β upregulates the MUC5AC mucin gene in part via the transcription factors NFκB while the glucocorticoid Dexamethasone (Dex) transcriptionally represses MUC5AC expression by Dex-activated GR binding to two GRE cis -sites in the MUC5AC promoter in lung epithelial cells. VBP compounds (ReveraGen BioPharma) maintain anti-inflammatory activity through inhibition of NFκB but exhibit reduced GRE-mediated transcriptional properties associated with adverse side-effects and thus have potential to minimize harmful side effects of long-term steroid therapy in inflammatory lung diseases. We investigated VBP15 efficacy as an anti-mucin agent in two types of airway epithelial cells and analyzed the transcription factor activity and promoter binding associated with VBP15-induced MUC5AC repression. VBP15 reduced MUC5AC mRNA abundance in a dose- and time-dependent manner similar to Dex in the presence or absence of IL-1β in A549 and differentiated human bronchial epithelial cells. Repression was abrogated in the presence of RU486, demonstrating a requirement for GR in the VBP15-induced repression of MUC5AC . Inhibition of NFκB activity resulted in reduced baseline expression of MUC5AC indicating that constitutive activity maintains MUC5AC production. Chromatin immunoprecipitation analysis demonstrated lack of GR and of p65 (NFκB) binding to composite GRE domains in the MUC5AC promoter following VBP15 exposure of cells, in contrast to Dex. These data demonstrate that VBP15 is a novel anti-mucin agent that mediates the reduction of MUC5AC gene expression differently than the classical glucocorticoid, Dex.